2020
DOI: 10.1093/infdis/jiaa747
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Ebola Exposure in Health Care Workers in Boende, Tshuapa Province, Democratic Republic of the Congo

Abstract: Healthcare workers (HCW) are more likely to be exposed to Ebola virus (EBOV) during an outbreak compared to people in the general population due to close physical contact with patients and potential exposure to infectious fluids. However, not all will fall ill. Despite evidence of subclinical and paucisymptomatic Ebola Virus Disease (EVD), the prevalence and associated risk factors remains unknown. We conducted a serosurvey among healthcare workers in the town of Boende in Tshuapa Province, Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…Thus, 1,366 individuals were included in this analysis. Subsections of this data have been used in previous publications [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, 1,366 individuals were included in this analysis. Subsections of this data have been used in previous publications [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Surveys were conducted in the participant’s preferred local language (French or Lingala), and data on sociodemographic and behavioral characteristics were collected. Data concerning potential exposures to EVD using previously defined criteria to describe direct, indirect and unlikely contact were also collected [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two studies analyzed more general populations in northwestern DRC: Lucas et al studied 19 market workers in Mbandaka, and revealed one individual seroreactive to EBOV GPe, but not to other ebolavirus GPs [ 17 ]. Doshi et al analyzed 582 health care workers (HCWs) who worked through the 2014 Boende EBOV outbreak, and detected 22.7% seroreactivity to EBOV GPe, but did not test other ebolavirus antigens [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…present especially in low-resources settings such as inadequate HCW training, insufficient PPE supplies, lack of diagnostic capabilities, and poor infrastructure of public health system [50].…”
Section: Review Articlementioning
confidence: 99%